Long-term nitric oxide inhibition and chronotropic responses in rat isolated right atria - Riado, Sonia R.; Zanesco, Angelina [UNESP]; Barker, Louis Allen; De Luca, Iara M.S.; Antunes, Edson; De Nucci, Gilberto (Wolters Kluwer, 1999)
The long-term administration of nitric oxide synthesis inhibitors induces arterial hypertension accompanied by left ventricular hypertrophy and myocardial ischemic lesions. Because the enhancement of sympathetic drive has been implicated in these phenomena, the current study was performed to determine the potency of β-adrenoceptor agonists and muscarinic agonists on the spontaneous rate of isolated right atria from rats given long-term treatment with the nitric oxide inhibitor N(ω)-nitro-L-arginine methyl ester (L-NAME). Atrial lesions induced by long-term treatment with L-NAME were also evaluated. Long-term L-NAME treatment caused a time-dependent, significant (P<0.05) increase in tail-cuff pressure compared with control animals. Our results showed that the potency of isoproterenol, norepinephrine, carbachol, and pilocarpine in isolated right atria from rats given long-term treatment with L-NAME for 7, 15, 30, and 60 days was not affected as compared with control animals. Addition of L-NAME in vitro (100 μmol/L) affected neither basal rate nor chronotropic response for isoproterenol and norepinephrine in rat heart. Stereological analysis of the right atria at 15 and 30 days revealed a significant increase on amount of fibrous tissues in L-NAME- treated groups (27±2.3% and 28±1.3% for 15 and 30 days, respectively; P<0.05) as compared with the control group (22±1.1%). Our results indicate that nitric oxide does not to interfere with β-adrenoceptor-mediated and muscarinic receptor-mediated chronotropic responses.
Keywords: Adrenergic receptor agonists; Blood pressure; Nitric oxide; Receptors, adrenergic, beta; Receptors, muscarinic; carbachol; isoprenaline; n(g) nitroarginine methyl ester; nitric oxide; noradrenalin; pilocarpine; adrenergic system; animal experiment; animal tissue; blood pressure measurement; chronotropism; concentration response; controlled study; drug potency; heart right atrium; nonhuman; priority journal; rat; Animals; Blood Pressure; Enzyme Inhibitors; Heart Atria; Male; Myocardial Contraction; NG-Nitroarginine Methyl Ester; Nitric Oxide; Nitric Oxide Synthase; Rats; Rats, Wistar; Sympathetic Nervous System; Ventricular Function, Right